Mode-of-action of the PROPELLA concept in fulminant myocarditis. (19th March 2019) - Spillmann, Frank; Van Linthout, Sophie; Schmidt, Gunther; Klein, Oliver; Hamdani, Nazha; Mairinger, Thomas; Krackhardt, Florian; Maroski, Bastian; Schlabs, Thomas; Soltani, Sajjad; Anker, Stefan; Potapov, Evgenij V; et al.
Abstract: Aims: Haemodynamic load induces cardiac remodelling via mechano-transduction pathways, which can further trigger inflammatory responses. We hypothesized that particularly in an inflammatory disorder such as myocarditis, a therapeutic strategy is required which, in addition to providing adequate circulatory support, unloads the left ventricle, decreases cardiac wall stress, and mitigates inflammatory responses. Methods and results: Axial flow pumps such as the Impella systems comply with these requirements. Here, we report a potential mode-of-action of prolonged Impella support (PROPELLA concept) in fulminant myocarditis, including a decrease in cardiac immune cell presence, and integrin α1, α5, α6, α10 and β6 expression during unloading. Conclusion: PROPELLA may provide benefits beyond its primary function of mechanical circulatory support in the form of additional disease-altering effects, which may contribute to enhanced myocardial recovery/remission in patients with chronic fulminant myocarditis.